The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1016/s0735-1097(84)80450-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propranolol and timolol on left ventricular volumes during exercise in patients with coronary artery disease

Abstract: The hemodynamic effects of beta-receptor blocking agents on the ejection fraction of patients with coronary artery disease during exercise have been studied previously using radionuclide techniques. Left ventricular volume measurements and the peak systolic pressure/end-systolic volume (PSP/ESV) index have been shown to be variables of left ventricular function that are less influenced by preload and afterload than is ejection fraction. Left ventricular volumes and PSP/ESV were therefore measured in 18 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Up to now, however, no study has analyzed the effect of these drugs on the exercise secretion of NPs. Exercising under beta-blockers leads to an increase cardiac preload, as evidenced by larger LV cavities at end diastole (31,32); thus, it may be wondered whether this also leads to an increase in wall tension or pressure high enough to trigger enhanced peptide release.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, however, no study has analyzed the effect of these drugs on the exercise secretion of NPs. Exercising under beta-blockers leads to an increase cardiac preload, as evidenced by larger LV cavities at end diastole (31,32); thus, it may be wondered whether this also leads to an increase in wall tension or pressure high enough to trigger enhanced peptide release.…”
Section: Discussionmentioning
confidence: 99%
“…In canine heart preparations DeGeest et al (1965) reported a lower systolic and an increased diastolic left ventricular (LV) pressure induced by vagal stimulation. Vagal blockade results in diminished LV diameters in dogs (Bishop & Horwitz, 1971), whereas ,-adrenoceptor blockade has the opposite effect, at least in humans (Chamberlain, 1966;Kalischer et al, 1984). Total autonomic nervous blockade causes a reduction in both stroke volume (SV) and LV ejection fraction (EF) at rest in healthy subjects, while cardiac output (CO) is maintained through relative tachycardia (Jose & Taylor, 1969;Kelbek et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In canine heart preparations DeGeest et al (1965) (Bishop & Horwitz, 1971), whereas ,-adrenoceptor blockade has the opposite effect, at least in humans (Chamberlain, 1966;Kalischer et al, 1984). Total autonomic nervous blockade causes a reduction in both stroke volume (SV) and LV ejection fraction (EF) at rest in healthy subjects, while cardiac output (CO) is maintained through relative tachycardia (Jose & Taylor, 1969;Kelbek et al, 1987).…”
Section: Introductionmentioning
confidence: 99%